Infrared action spectroscopy of nitrous oxide on cationic gold and cobalt clusters - Cunningham, EM; Green, AE; Meizyte, G; Gentleman, AS; Beardsmore, PW; Schaller, S; Pollow, K; Saroukh, K; Förstel, M; Dopfer, O; Schöllkopf, W; Fielicke, A; et al. (Royal Society of Chemistry, 2020)
Understanding the catalytic decomposition of nitrous oxide on finely divided transition metals is an important environmental issue. In this study, we present the results of a combined infrared action spectroscopy and quantum chemical investigation of molecular N2O binding to isolated Aun+ (n ≤ 7) and Con+ (n ≤ 5) clusters. Infrared multiple-photon dissociation spectra have been recorded in the regions of both the N[double bond, length as m-dash]O (1000–1400 cm−1) and N[double bond, length as m-dash]N (2100–2450 cm−1) stretching modes of nitrous oxide. In the case of Aun+ clusters only the ground electronic state plays a role, while the involvement of energetically low-lying excited states in binding to the Con+ clusters cannot be ruled out. There is a clear preference for N-binding to clusters of both metals but some O-bound isomers are observed in the case of smaller Con(N2O)+ clusters.